The Coaches` Eye: Exploring coach decision-making during talent identifikation - Roberts, A. H. (2021)
For decades, researchers and practitioners interested in talent identification have discussed the coaches` eye: the elusive ability that allows some coaches to `see` qualities in an athlete that point to their talent or future potential. While there is significant anecdotal evidence of coaches who possess this ability, there is little empirical research supporting the validity or reliability of the coaches` eye. Guided by ecological dynamics, this thesis employs mixed methodologies to explore the decision-making that underpins how high-level coaches identify talent in Olympic combat sports. These four studies captured the processes of thirtyfour coaches during the talent identification process, exploring and identifying the factors that impact on a coach`s ability to perform this integral task. A systematic review and meta-synthesis revealed that `instinct` is a primary contributor to coach decision-making during talent identification (TID), allowing coaches to `know it when they see it`. Semi-structured interviews with international coaches explored this `instinct` during TID and revealed that coaches require experience, time and knowledge of context in order to identify talent. An instrumental case study corroborated these results, and also found that there is a significant conceptual difference between talent identification and talent selection, in the eyes of this coach. Both studies indicated that coaches likely select athletes based on their capabilities as a coach, not purely on athlete ability or potential. The final study found that nine national-level coaches did not agree on the rankings of talented youth judo athletes after four days. This finding indicates that the coaches` eye is subjective and confirms the novel findings of the prior studies; namely that coaches require time to get to know athletes, their opinions of the athletes` talent changed over time, and coaches vary in who they `see` as talented. Finally, two new models are presented: the Coach-Informed Talent Identification Process and a novel model of the Coaches` Eye in Talent Identification.